2014
DOI: 10.1177/0022034514545629
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Affects Enamel Protein Content via TGF-β1-mediated KLK4 Inhibition

Abstract: Dental fluorosis is caused by chronic high-level fluoride (F -) exposure during enamel development, and fluorosed enamel has a higher than normal protein content. Matrix metalloproteinase 20 cleaves enamel matrix proteins during the secretory stage, and KLK4 further cleaves these proteins during the maturation stage so that the proteins can be reabsorbed from the hardening enamel. We show that transforming growth factor β1 (TGF-β1) can induce Klk4 expression, and we examine the effect of F -on TGF-β1 and KLK4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…The effect of TGF-β on maturation and mineralization processes may also be achieved indirectly, since it modulates expression of kallikrein-related peptidase-4 (KLK-4) and matrix metalloproteinase-20 (MMP-20) [Cho et al, 2013;Gao et al, 2009;Suzuki et al, 2014], two important enzymes required for enamel matrix protein degradation during development, which allows hydroxyapatite crystal mineralization and growth. MMP-20 is secreted by ameloblasts during the secretory phase, ensuring enamel appositional growth [Bartlett, 2013], while KLK-4 is secreted by mature ameloblasts and its function is to reabsorb protein degradation products, promoting mineral deposition as enamel hardness increases [Hu et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of TGF-β on maturation and mineralization processes may also be achieved indirectly, since it modulates expression of kallikrein-related peptidase-4 (KLK-4) and matrix metalloproteinase-20 (MMP-20) [Cho et al, 2013;Gao et al, 2009;Suzuki et al, 2014], two important enzymes required for enamel matrix protein degradation during development, which allows hydroxyapatite crystal mineralization and growth. MMP-20 is secreted by ameloblasts during the secretory phase, ensuring enamel appositional growth [Bartlett, 2013], while KLK-4 is secreted by mature ameloblasts and its function is to reabsorb protein degradation products, promoting mineral deposition as enamel hardness increases [Hu et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with studies showing that fluoride inhibits the expression of the key enamel proteases and modulates that of other genes involved in mineralization. (18,29,42,43) In addition, NaF may also affect the extracellular compartment by controlling the assembly of amelogenin nanospheres and the mineralization process. (43) Indeed, we found that NaF perturbed gene expression to the highest extent during the maturation stage of ameloblasts, consistent with previous data.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride decreases KLK4 and TGF-β1 transcript and protein levels that are necessary for enamel formation (Suzuki et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%